2016
DOI: 10.1159/000447327
|View full text |Cite
|
Sign up to set email alerts
|

The Lectin Complement Pathway in Patients with Necrotizing Soft Tissue Infection

Abstract: Background: Mannose-binding lectin (MBL) and ficolins are pattern recognition molecules (PRMs) that play an important role during infection through activation of the lectin complement pathway. We assessed whether plasma PRM levels were associated with mortality in patients with necrotizing soft tissue infection (NSTI). Methods: We conducted a prospective, observational study over 25 months involving 135 NSTI patients with a maximum follow-up of 2.7 years. Blood samples were taken upon admission. Non-infected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…We have previously examined several complement system associated pattern recognition molecules (PRMs) such as CRP, Pentraxin-3, MBL, ficolin-1, ficolin-2, and ficolin-3 as biomarkers for risk stratification in the same cohort of NSTI patients (13,19). In the survival analysis, ficolin-2 was the most promising of the above-mentioned PRMs, but the association with mortality disappeared after adjusting for SAPS II (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously examined several complement system associated pattern recognition molecules (PRMs) such as CRP, Pentraxin-3, MBL, ficolin-1, ficolin-2, and ficolin-3 as biomarkers for risk stratification in the same cohort of NSTI patients (13,19). In the survival analysis, ficolin-2 was the most promising of the above-mentioned PRMs, but the association with mortality disappeared after adjusting for SAPS II (13).…”
Section: Discussionmentioning
confidence: 99%
“…The complement system is divided into three converging proteolytic cascades; the classical, the lectin, and the alternative pathways. We have previously investigated the use of the lectin pathway initiator molecules and kinetic complement analyses as prognostic markers in NSTI patients (13), suggesting that pattern recognition molecules of the lectin pathway play an important role in these patients. Here, we further investigate the levels the lectin pathway associated enzymes MASP-1, MASP-2, MASP-3, the down-stream components C4, C3, the complement activation products C4c, C3bc, and the fluid phase analog of the terminal C5b-9 complement complex (TCC) in NSTI patients and a group of non-infected control patients.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, published in this issue, the authors show that stimulation of the histamine H4 receptor and the IL-4 receptor, respectively, decreases expression of the anaphylatoxin C3a receptor. As complement activation is one of the first innate immune responses leading to a number of different host responses [16, 18-20], the authors concluded that their data are relevant in the assessment of histamine receptor antagonists in clinical trials for atopic dermatitis and other inflammatory skin diseases including psoriasis [17]. Though these are only four examples out of nine articles published in this issue, they highlight the diversity of the innate immune system and provide you with the thought that there is much more to explore.…”
mentioning
confidence: 99%
“…Ultimately, these events merge with the amplification loop of the alternative pathway. This emphasizes the key importance of complement, with several pathways to cause activation, resulting in the subsequent immune responses including the opsonization of bacteria, the promotion of chemotaxis, phagocytosis, and bacterial killing executed by the neutrophils [2][3][4].…”
mentioning
confidence: 99%